Mendayung (Memanipulasi Wacana) di Antara Dua Karang: Discursive hedging Indonesia dalam Indo-Pasifik - Kevin Ali Sesarianto (Department of International Relations, Hasanuddin University, 2023)
In the Indo-Pacific constellation which targets political, security and economic issues, Indonesia is constructed as a middle power country. This construction originates from the political reality that Indonesia must hedge between the influence of the United States and China. In other words, the Indo-Pacific is a construction in which there are conflicting interests of the two great powers. Using the postcolonial critical discourse analysis method, this paper explores the construction that Indonesia is doing in ASEAN regarding the Indo-Pacific, namely the ASEAN Outlook on the Indo-Pacific. This paper looks at two important things: (1) the discursive power relations embodied in Indo-Pacific discourse and (2) the activity of manipulating discourse so that Indonesia is merely in a